Improved Decadal Predictions of North Atlantic Subpolar Gyre SST in CMIP6. Issue 3 (28th January 2021) - Borchert, Leonard F.; Menary, Matthew B.; Swingedouw, Didier; Sgubin, Giovanni; Hermanson, Leon; Mignot, Juliette
Abstract: Due to its wide‐ranging impacts, predicting decadal variations of sea surface temperature (SST) in the subpolar North Atlantic remains a key goal of climate science. Here, we compare the representation of observed subpolar SST variations since 1960 in initialized and uninitialized historical simulations from the 5th and 6th phases of the Coupled Model Intercomparison Project (CMIP5/6). Initialized decadal hindcasts from CMIP6 explain 88% of observed SST variance post‐1980 in the subpolar gyre at lead years 5–7 (77% in uninitialized simulations) compared to 42% (8%) in CMIP5, indicating a more prominent role for forcing in driving observed subpolar SST changes than previously thought. Analysis of single‐forcing experiments suggests much of this correlation is due to natural forcing, explaining ∼55% of the observed variance. The amplitude of observed subpolar SST variations is underestimated in historical simulations and improved by initialization in CMIP6, indicating continued value of initialization for predicting North Atlantic SST. Plain Language Summary: Sea surface temperature (SST) fluctuations in the North Atlantic region are known to influence climate around the globe. Comparing retrospective predictions of North Atlantic SST with observations, we show that the most state‐of‐the‐art climate models have improved in predicting North Atlantic SST for up to 10 years ahead compared to the previous generation of climate models. This recent improvement can be traced back to particularly well‐predicted variations of North Atlantic SST after 1980. During this time, reactions to large volcanic eruptions and changes in solar activity, as well as inherent unforced variations, play an important role for the predictability of North Atlantic SST. Here, not only direct radiative forcing changes play a role, but there is also a dynamical response of the ocean that influences the final climate response. This study inspires hope that current climate models will show improved capability in predicting North Atlantic SST changes up to a decade ahead, particularly following large volcanic eruptions, but also otherwise. Key Points: North Atlantic sea surface temperature (SST) is better predicted in CMIP6 than in CMIP5 in both initialized hindcasts and noninitialized historical simulations High correlation of North Atlantic SST in CMIP6 historical simulations with observations indicates a prominent role for forcing after 1980. Fifty‐five percent of the total observed post‐1980 annual North Atlantic SST variance is explained by simulations with natural forcing only